Acceptance Cumulative Sum Control Charts: Overview of Basic Tools - Major, Michał (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The main goal of this article was to review and analyse basic cumulative sum control charts, which can be used to accept or disqualify an analysed production process. In the literature, there are two kinds of acceptance control charts: Shewhart Control Charts and Cumulative Sum Control Charts (CUSUM Charts). Both can be used by quality managers or financial managers in monitoring or auditing processes. The article presents only selected process control procedures. The conclusion of the article provides examples of the applications of the solutions described.